Leveraging adaptive approaches to tackle opportunity gaps in STEM higher education - Wilson-Kennedy, Zakiya S.; Payton-Steward, Florastina (Frontiers in Education, 2025)
Many institutions in the United States are struggling with opportunity gaps that disproportionately affect key populations within their communities. As national conversations about the legacies of racism and other forms of systemic bias in higher education continue, they are being met with strong resistance in the form of anti-DEI (Diversity, Equity, and Inclusion) and anti-WOKE policy agendas. While acknowledging the existence of these opportunity gaps is an important first step, it is crucial to develop strategic approaches that are adaptable to the changing national context in order to foster systemic change. These ongoing challenges are often viewed as technical issues that require an expert to step in as a change leader. However, technical approaches do not lead to transformational change. To achieve transformational institutional change, stakeholders must be engaged in adaptive and cultural change efforts. This is particularly relevant in today's climate of culture wars. The Four-Frame Model for academic leadership provides a strategy for reframing how persistent challenges should be approached in higher education. This perspective article explores how this model may be employed for transformative leadership in addressing systemic opportunity gaps.